Recursos territoriais e escalas de poder no processo de renovação da concessão da ponte da integração de São Borja-BRA/ San Tomé-ARG (2021-2023) - Muriel Pinto; Domingos Sávio Campos de Azevedo (Confins)
The São Borja-Brazil/San Tomé – Argentina integration bridge opened in 1997 created great expectations of integration and economic development for the border communities on the banks of the Uruguay River. The appropriate bridge was built and the CUF was created – the first Unified Mercosur border center. Currently, the flow of international trade in this customs department represents around 30% of the trade balance between Argentina and Brazil, being a strategic corridor for trade, tourism and regional integration. The study problematized how the scales of power and territorial resources occurred in the processes of renewing the concession of the São Borja-BRA/San Tomé-ARG integration bridge (2021-2023). To this end, literature reviews were carried out, the methodology of geographic scales of power and analysis of journalistic discourses were applied. As main results, it is observed that the due process of concession occurred in periods of diplomatic disagreements and lack of dialogue between the Governments of Brazil and Argentina, a leading role on the national scale in terms of actors and interests was noted, however the local scale did listen to regional demands and presented the bridge scenario with the centralities of power, being an articulating and cooperative scale between Local-national; International-local; and local-regional. The place and its actors presented institutional cohesion in defense of priority agendas for the region, decentralization between territorial actors in relation to the arenas and interests in the process. In relation to territorial innovation, it is worth highlighting that the bridge and its structure have expertise in the area of ​​international trade and agility in processes, in addition to public universities and a geostrategic location in Prata.